ДИН САЛАСЫНДАҒЫ РЕФОРМАЛЫҚ ИЛАЖЛАР - ТЫНЫШЛЫҚ ҲӘМ АЎЫЗБИРШИЛИКТИ БЕККЕМЛЕЙДИ - Якубов, М.; Абаев, С. (SCIENCE and SOCIETY, 2019)
The article deals with the significant and effective work implemented in Uzbekistan under the supervision of President Shavkat Mirziyoyev directed to fulfillment of religious tolerance and fundamental development of the religious-educational activity carried out in our country in the recent years.
Keywords: religion; religious-educational activity; tolerance; Islamic civilization; Islamic Academy